The effect of work-life balance, work stress, and workload on employee performance with organizational support as moderation variables - Edwin Syahada, Levania; Suhardi; Firdaus, Rahmad (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the influence of work-life balance, work stress, and workload on employee performance, with organizational support as a moderation variable. A good work-life balance is expected to improve employee performance, while work stress and high workload tend to lower productivity. Organizational support plays a role in strengthening or weakening the relationship between these variables on employee performance. This study uses a quantitative approach with a survey method involving 183 employees in certain sectors. Data were collected through questionnaires and analyzed using the moderation regression technique. The results of the study show that work-life balance has a positive effect on employee performance, while work stress and workload have a negative effect. In addition, organizational support has been shown to moderate the relationship between work stress and employee performance, as well as between workload and employee performance, by providing a mitigating effect against the negative impact it causes. These findings underscore the importance of organizational policies in creating an optimal work-life balance and providing adequate support to improve overall employee performance